Association between Sarcopenia and Metabolic Syndrome in Chronic Obstructive Pulmonary Disease: The Korea National Health and Nutrition Examination Survey (KNHANES) from 2008 to 2011. (1st February 2015) - Chung, Jae Ho; Hwang, Hee-Jin; Han, Chang Hoon; Son, Bong Soo; Kim, Do Hyung; Park, Moo Suk
Abstract: Aim: It is not clear whether the restrictive or obstructive pattern of spirometry is associated with metabolic syndrome. We investigated the associations between restrictive and obstructive spirometric patterns and metabolic risk factors using data from the Korea National Health and Nutrition Examination Survey (KNHANES). Additionally, we investigated whether sarcopenia is associated with metabolic syndrome in patients with chronic obstructive pulmonary disease (COPD). Methods: Using data from KNHANES between 2008 and 2011, we enrolled 8, 145 subjects (normal lung function: 6, 077, obstructive spirometric pattern: 1, 039, restrictive pattern: 1, 029) aged ≥40 years who underwent anthropometric measurement, laboratory tests, spirometry and estimation of appendicular muscle mass. Sarcopenia was defined as an appendicular skeletal muscle mass divided by body weight squared <2 SD below the sex-specific mean for the young reference group. Results: Sarcopenia was found in 32.8% of male and 12.2% of female patients with COPD. The odds ratio (OR) of metabolic syndrome for the restrictive spirometric pattern in male was 1.29 (95% confidence interval [CI], 1.02–1.65), and that for obstructive pattern in males was 0.99 (95% CI, 0.79–1.26) after adjustments for covariables (female restrictive pattern (ORs, 1, 45; 95% CI, 1.09–1.91) and female obstructive pattern (ORs 0.73; 95% CI, 0.49–1.09). After adjustment for other confounding factors, the risk of metabolic syndrome was higher in sarcopenic male (OR, 1.88; 95% CI, 1.27–2.77) with COPD than in those without sarcopenia. Conclusions: The restrictive spirometric pattern is associated with metabolic syndrome, and sarcopenia may contribute to the risk of metabolic syndrome in male patients with COPD.